Short communicationCoronary spasm that caused non-ST elevation myocardial infarction appeared in cath lab due to vasovagal reaction - Sreckovic, Miodrag Jovan; Jagic, Nikola; Zdravkovic, Vladimir; Nikolic, Dusan; Tasic, Mladen; Sreckovic, Ana Maksimovic; Miloradovic, Vladimir (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Coronary artery spasm is sometimes an unrecognized cause of myocardial ischemia. Myocardial ischemia is not always a product of fixed stenosis; it can also be induced by dynamic, transient stenosis. The angiogram represents the current state of vasculature at the time of examination and absence of stenosis does not mean disease absence. We present a case of right coronary artery spasm that caused non-ST elevation myocardial infarction and arrhythmias and was induced again in the cath lab due to vasovagal reaction.